METODE KINDERGARTEN WATCHING SIAGA BENCANA GEMPA BUMI TERHADAP STIMULASI KECERDASAN VISUAL SPASIAL DAN KECERDASAN KINESTETIK ANAK USIA DINI DI TK SYEIKH ABDURRAUF BLANG OI BANDA ACEH - Lina Amelia (JURNAL TEMATIK, 2015)
The purpose of this study was to determine (a) Implementation of the method Kindergarten watching Earthquake Preparedness can be applied by early childhood educators in kindergarten Sheikh Abdurrauf Blang Oi of Banda Aceh, (b) Methods of Kindergarten watching Earthquake Preparedness able to give effect to the Visual Spatial intelligence and kinesthetic child in kindergarten Sheikh Abdurrauf Blang Oi of Banda Aceh. This type of research is the development of research (Research and development/R & D) 4-D models ( define, design, develop and disseminate). This study was conducted in kindergarten Sheikh Abdurrauf Blang Oi of Banda Aceh with the population and sample research is TK B total of 38 children. This research was carried out for 2 months beginning with the initial survey instrument to school and discussions with teachers and test instrument October, research in 17 to 22 November 2014, resumed last date of 6-10 January 2015 data processing is done in January-February 2015. The instrument used in this study is an informal test sheets for children, observation sheets visual spatial abilities of children, teacher observation sheets and sheets impression guru.teknik data analysis is to use a statistical formula, in this study because it used a single sample test formula t for a single group. Based on the results of the calculation of the t value obtained 8.070 while the value t table is 2.028 so that t is greater than t table t>t table, 8.070>2.028 so it can be concluded that there are significant watching kindergarden learning to stimulation of visual spatial intelligence and kinesthetic child. This data is also strengthened by the observation of the child more memrikan positive responses than negative responses. Overall it can be concluded that children who give a positive response are 32 people from 38 children (84.21%) and negative responses 6 of 38 children (15.79%)